The Dialogue Character of Pedagogical Relation (Training and Practice : Journal of Educational Sciences, 2007)
A special form of interpersonal communication is realised during the intercourse between teachers and students. In the course of pedagogical communication the primary factor maintaining dynamism is strategy, which provides the basis and structure of communication. This study points out that it is the cooperative strategy, and especially a typical form of it, the dialogue, which comes closest to the essence of teaching-learning. The pedagogical relation obtains its real meaning from having the character of a dialogue.